STRATEGI PENGEMBANGAN AYAM RAS PETELUR DI KOTA SAMARINDA KALIMANTAN TIMUR - Herdianto Kurniawan; Budi Guntoro; Wihandoyo (Wihandoyo) (Faculty of Animal Science, Universitas Gadjah Mada, 2011)
The study was aimed to identify and to analyze the strengths, weaknesses, opportunities and threats that facedthe city of Samarinda in fulfilling the egg need and to formulate the best and suitable strategy for the region to face theshortage of egg supply. The study was conducted in November 2009. The method used in the study was descriptive analysis method. Methods of data collection using questionnaires, interviews, observation and literature study. Methodsof data analysis using the SWOT analysis (strengths, weaknesses, opportunities, threats) were used to identify the internal environmental factors (strengths and weaknesses) and external environmental factors (opportunities and threats) areas. The result was then drawn in the quadrant analysis of SWOT and interpreted in the SWOT matrix could be to show the position and direction of regional development as well as alternative strategies that can be run. The results showed that internal identified value was 0.3922 and the external identified value was 0.0308. Development strategy at Samarinda in the first quadrant with a strengths was greater than the opportunities, so the region must be able to use these strengths to take advantage of existing opportunities. The area should implement an aggressive growth strategy (growth oriented strategy) in order to meet the self need of eggs in the region Samarinda.(Key word: Layer, Development strategy, SWOT analysis)